2019
DOI: 10.3390/educsci9040299
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Gamification and Flipped-Classroom Program for Teachers in Training on Motivation and Learning Perception

Abstract: We present the results of a training program with future Primary Education teachers on the impact on motivation and perception of learning achieved through strategies and techniques associated with gamma and flipped-classroom. The program was run in four classroom groups (n = 210) at the University of Murcia (Spain) and the aim was to analyze the effect that the gamification-based and flipped-classroom program has on motivation and learning. Information was collected through a perceptions questionnaire. Descri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
2
15

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(77 citation statements)
references
References 72 publications
4
32
2
15
Order By: Relevance
“…The result of the Cronbach's alpha test of the validity of the instrument used in this study was 0.895, as can be seen in Table 1. This reliability procedure was used in the same way as in other studies in the field of social sciences teaching, such as Getsdóttir, van Boxtel, and van Drie [34] or Gómez-Carrasco, Monteagudo, Moreno-Vera, and Sáinz [19]. The criterion established by various authors is that a Cronbach's alpha value between 0.70 and 0.90 indicates a good internal consistency of the questionnaire items for a unidimensional scale [35].…”
Section: Validation and Analysis Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…The result of the Cronbach's alpha test of the validity of the instrument used in this study was 0.895, as can be seen in Table 1. This reliability procedure was used in the same way as in other studies in the field of social sciences teaching, such as Getsdóttir, van Boxtel, and van Drie [34] or Gómez-Carrasco, Monteagudo, Moreno-Vera, and Sáinz [19]. The criterion established by various authors is that a Cronbach's alpha value between 0.70 and 0.90 indicates a good internal consistency of the questionnaire items for a unidimensional scale [35].…”
Section: Validation and Analysis Proceduresmentioning
confidence: 99%
“…In this respect, Cuenca [12] highlights the necessity of breaking down the educational and methodological barriers [19] that have restricted the didactic potential of heritage. He advocates taking full advantage of all the possibilities that heritage education offers in order to teach citizens to be respectful of their past and, thereby, their present.…”
Section: Introductionmentioning
confidence: 99%
“…However, it must be recognized that other technologies are increasingly being incorporated into this teaching strategy, such as augmented reality (Sánchez-García & Toledo-Morales, 2017), social networks (Blasco-Serrano et al, 2018), or gamification (Gómez-Carrasco et al, 2019).…”
Section: Teaching-learning and The Importance Of Materials In Flipped Classroommentioning
confidence: 99%
“…Pre-teachers' perceptions of gamification have already been studied in the literature. For example, Gómez-Carrasco et al (2019) administered a questionnaire to examine perceptions of gamification used in a flipped classroom among 20 pre-teachers. The findings showed that the pre-teachers were motivated, and their learning was successful.…”
Section: Students' Perceptions Of Gamificationmentioning
confidence: 99%